Effectiveness of hypnotherapy in school children with disorders of phobic anxiety - Adolfo Rafael Lambert Delgado; Ariane Hernández Trujillo; Wilvian Ernesto Cobas Contreras; Alberto Erconvaldo Cobián Mena; José Luis Reyes Escalona (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: Phobia is an anxiety disorder characterized by fear or intense and irrational fear toward something. It presents an annual rate of incidence of 8 % and hypnosis is one of the most used treatments in those who suffer from this disorder. Objective: To evaluate the effectiveness of the hypnotherapeutic pattern applied to patients in school age with phobic anxiety disorders. Methods: A quasi-experiment hypnotherapeutic intervention was carried out in the 30 patients with school phobia that attended the hypnosis multidisciplinary service at the Therapeutic Hypnosis Clinic in Santiago de Cuba, from October, 2016 to the same month in 2018. To such an effect, the intervention consisted of 3 stages and the Mc-Nemar test was applied for 2 related samples, as well as the chi-square test. Results: In the series there was a prevalence of the male sex patients (53.3 %), mainly between 8 and 9 years (37.5 %), as well as the specific phobias. After having applied the hypnosis, a favorable psychological response was obtained in all the patients.  Conclusions: The hypnotherapeutic pattern applied was effective, because a favorable clinical course and a good treatment response were achieved.